2015
DOI: 10.1007/s11427-015-4835-2
|View full text |Cite
|
Sign up to set email alerts
|

Genomic variation in the hybrids of white crucian carp and red crucian carp: evidence from ribosomal DNA

Abstract: In this study, we conducted a cross of white crucian carp (♀)×red crucian carp (♂) (WR), and characterized the morphology, reproduction and genetics of the progeny. Different from parents, WR with the gray color showed the hybrid morphological traits of both parents. WR possessed normal gonads producing mature eggs or sperm, and exhibited high fertilization rate (90.2%) and high hatchery rate (80.5%), which contributed to produce and enlarge the population. WR with the same DNA content as parents was a diploid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…(Figure 1A and B). One type of F 1 hybrid was obtained in the present study, which was diploid (2n=100), as previously reported (Wang et al, 2015). The diploid hybrid was bisexually fertile showing a normal pattern of gamete development (Figure 1C).…”
Section: Formation Of Experimental Fishsupporting
confidence: 84%
See 3 more Smart Citations
“…(Figure 1A and B). One type of F 1 hybrid was obtained in the present study, which was diploid (2n=100), as previously reported (Wang et al, 2015). The diploid hybrid was bisexually fertile showing a normal pattern of gamete development (Figure 1C).…”
Section: Formation Of Experimental Fishsupporting
confidence: 84%
“…The diploid hybrid was bisexually fertile showing a normal pattern of gamete development (Figure 1C). Meanwhile, as previously reported (Wang et al, 2015), an F 2 population was created by F 1 self-crossing (Figure 1D).…”
Section: Formation Of Experimental Fishmentioning
confidence: 64%
See 2 more Smart Citations
“…Distant hybridization is an important technique and widely used in fish genetic breeding, which can combine whole genomes from parent species and lead to changes in both phenotypes and genotypes in the offspring ( Liu, 2010 ; Zhang et al, 2014 ; Xu et al, 2015a ). For example, in terms of phenotypes, the allodiploid lineage with hybrid traits, high survival rate, good meat quality, and strong stress resistance were established by the distant hybridization of Japanese white crucian carp ( Carassius cuvieri , ♀) and red crucian carp ( Carassius auratus red var., ♂) ( Wang et al, 2015 ; Liu et al, 2017 , 2018 , 2019a , b ); the triploid fish with fast growth were produced by the crossing of diploid fish with allotetraploid fish ( Tiwary et al, 2004 ; Zhong et al, 2012 ; Wang et al, 2020 ); in terms of genotypes, a high proportion of chimeric genes (>9%) have been found among orthologous genes in the transcriptomes of allotetraploid fish ( Liu et al, 2016 ); many different expressed genes associated with sperm flagellar assembly and motility were found in testis transcriptomes from diploid fish and triploid fish ( Xu et al, 2015b ; Li et al, 2018a ). These phenotypes and genotypes are very important for breeding applications and scientific research.…”
Section: Introductionmentioning
confidence: 99%